2021
DOI: 10.1021/acs.oprd.1c00058
|View full text |Cite
|
Sign up to set email alerts
|

From Milligram to Kilogram Manufacture of AZD4573: Making It Possible by Application of Enzyme-, Iridium-, and Palladium-Catalyzed Key Transformations

Abstract: With the first generation medicinal chemistry synthesis as a starting point, we describe herein process development of AZD4573, an oncology drug candidate. In addition to improved yields and removal of chromatographic steps, we have addressed other factors such as availability of starting materials as well as safety of the chemistry involved. With several steps involving volatile, reactive, and non-UV active materials, reaction optimization was facilitated by implementing off-line 1H NMR analysis of crude mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Furthermore, Tf 2 NPh and the resulting sulfonamide byproduct were difficult to remove by crystallization and carried over into isolated triflate 6 . For these reasons, replacing this reagent with a common reagent, Tf 2 O, was investigated . However, the reaction of pyridone 5 with Tf 2 O and Et 3 N in THF or MeCN gave a complex mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Tf 2 NPh and the resulting sulfonamide byproduct were difficult to remove by crystallization and carried over into isolated triflate 6 . For these reasons, replacing this reagent with a common reagent, Tf 2 O, was investigated . However, the reaction of pyridone 5 with Tf 2 O and Et 3 N in THF or MeCN gave a complex mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of AZD4573 ( 35) demonstrated the superiority of CÀ H activation/borylation over prefunctionalization and palladium-catalyzed borylation on a large scale (Scheme 9). [42] In order to rapidly provide AZD4573 (35), an oncology drug candidate, in sufficient quantities for preclinical and clinical studies, several steps of the medicinal chemistry route had to be modified. One of the changes was the borylation step.…”
Section: Iridiummentioning
confidence: 99%
“…The synthesis of AZD4573 ( 35 ) demonstrated the superiority of C−H activation/borylation over prefunctionalization and palladium‐catalyzed borylation on a large scale (Scheme 9). [42] …”
Section: Preparative Scale Applications Of C−h Activation In Medicina...mentioning
confidence: 99%
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%